The material relating to the anatomy of Rhaponticum serratuloides leaf blades according to age conditions - Mamyrova, S.A.; Andreev, B.G.; Kupriyanov, A.N.; Kubentaev, S.A. (Fundamental and Experimental Biology, 2024)
In the article the features of the morphological and anatomical structure of leaf blades in the process of ontogenesis of Rhaponticum serratuloides Georgi (Bobr.) during juvenile, immature, virginal, generative and senile age states were presented. It was noted that as the plant matures, the degree of dissection and linear dimensions of the leaf blades, as well as their vascular bundles and trichomes, increase. It was established that in the juvenile and immature periods of development whole and elliptical leaves predominate. In the virginal state, in addition to the typical entire leaves, leaves with an unpaired pinnate leaf blade appear. The generative state of Rh. serratuloides is characterized by having upper leaves as entire, sessile; the lower ones are petiolate, pinnately lobed with a large apical lobe. In the senile state, leaves of immature and virginal types are found. General patterns of leaf internal structure of Rh. serratuloides and another representative of the same genus Rh.carthamoides Willd (Iljin) were revealed as following: the plants are of dorsal-ventral type of leaf blade structure, with collateral vascular bundles of a closed type with a sclerenchyma covering and leaf pubescence. Along with this, characteristic diagnostic features for leaves of Rh. serratuloides were described as the following: the absence of capitate glands and long cord-like hairs during all age states, the presence of air-bearing cavities in the parenchyma of virginal and senile plants, associated with the habitat of the plant under study, because it grows in flooded meadows, along the shores of lakes and swamps.